Extraction of Natural Pigments from Hylocereus Polyrhizus Grown In Malaysia - Naderi, Nassim (2009)
The use of natural colors in food is gaining importance because the number of synthetic colorants approved for use in food is legislatively restricted. There is only one type of betacyanin i.e. betanin has been approved as natural food colorant (E-162) and almost entirely obtained from the red beet. Thus, in this study Hylocereus polyrhizus fruit, as an alternative source of betacyanin pigments was investigated to meet the ever-increasing commercial demand. Two solvent extraction systems were investigated to determine the efficiency of solvents in recovering color pigments from pulp of Hylocereus polyrhizus fruit. Individual betacyanin pigments were identified according to High-performance liquid chromatographic analysis. Quantitative and qualitative differences were determined in betacyanin composition of each concentrated extract. Betanin, phyllocactin, hylocerenin and their respective isomers with different ratios were the major betacyanin components of Hylocereus polyrhizus fruits. From solvent system selection, the aqueous ethanolic system was found more effective than ethanol in recovering betacyanins. The alteration of betanin:phyllocactin peak area ratio in ethanolic assay revealed the lower stability of phyllocactin that resulted deacylation and betanin formation. Enzymatic treatment method was optimized by means of highest yield of pigment in concentrated extract. Betacyanin retention was monitored in a range of different enzyme dosage (0.1%-2% w/v). The color characteristic of concentrated extracts from solvent extraction assays and enzymatic treatment were compared and monitored along with red beet colorant by using CIELAB system. Chroma (C*) value was strongly influenced by applied extraction methods. The two extracts obtained from the pulp of fruits by solvent extraction assay provided color tint (ho) close to the red beet color. Tonality of color extracts from the skin and enzyme-treated shifted into an intense purple color and due to their chroma value displayed darker color. These findings revealed that composition of betacyanin pigments in Hylocereus polyrhizus fruit displayed wider color spectrum compare to red beet. Application of betacyanins in Hylocereus polyrhizus fruit could have considerable potential for development to be employed in the food industry.